An investigation into the impact of perceived narcissistic leadership on employees’ organisational deviance in organisations located in the U.K. - Syed, Amani (2020)
Research on narcissistic leadership has been predominantly concerned with the behavioural characteristics associated with narcissism and the effect of leader narcissism on the leader themselves. Few studies have considered the impact of leader narcissism on follower outcomes or behaviours. Taking into account Bandura’s (1999) social cognitive theory of moral disengagement, this quantitative study investigates the relationship between perceived narcissistic leadership and employees’ organisational deviance, considering the role of moral disengagement as a mediator. Using an online survey, 80 responses were received from employees working in organisations located in the U.K. Data obtained from the survey was analysed using correlation analysis and regression. Findings from this study supported the assumption that perceived narcissistic leadership is positively related to instances of employees’ organisational deviance. The mediating effect of moral disengagement between perceived narcissistic leadership and employees’ organisational deviance was not supported in this study. The results of this study also shown that perceived leader narcissism significantly predicted employees’ organisational deviance, suggesting that organisations led by narcissistic managers may be less ethical. Employees and managers would do well to consider leader narcissism and its behavioural consequences in organisations located in the U.K.